Моделювання впливу струмів витікання в ЛАЦП з перерозподілом заряду - Мичуда, З.; Мичуда, Л. (Видавництво Національного університету “Львівська політехніка”, 2005)
The mathematical models of errors of logarithmic ADC, based on the effect of recharge in condensers cells, are offered, the results of modelling are presented and the valuation of accuracy are given.
Keywords: 621.335 (088.8)